Keragaan Agronomi Rumput Gajah (Pennisetum purpureum cv Taiwan) Hasil Irradiasi Sinar Gamma: The Agronomic Performance of Elephant Grass (Pennisetum purpureum cv Taiwan) Resulted from Gamma-ray Radiation) - Harmini Harmini; S Sajimin; A Fanindi; A Husni (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2020)
The objective of this study was to determine the agronomic diversity of gamma-ray at 50 Gray dose during the phase of embryogenetic callus in napier grass cv Taiwan. This research used a randomized blok design (RBD) of gamma-ray and without radiation elephant grasses (P. purpureum cv Taiwan). There were 51 numbers in irradiated elephant grass, each number three replicated and five plant per number each. Without irradiation control used elephant grass (P. purpureum cv Taiwan); there were 10 clumps in one block and each line number had been repeated three times. Gamma radiation showed no impact on plant height and stem weight (dry weight) at P>0.05, but had a significant effect on number of tillers, leaf length, leaf width, total weight, fresh weight, leaf (dry weight), weight of stem (fresh weight). Gamma ray irradiation selection does not have to generate high output but can be developed on sub optimal soil or extreme weather conditions such as tolerant felling, which requires less high plant. Key words: diversity, forage, irradiation